Entry, egress and vertical transmission of SARS-CoV-2 - Zhang, Hui (J Mol Cell Biol, 2021)
The high infectivity and pathogenicity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have caused the COVID-19 outbreak, one of the most devastating pandemics in more than a century. This pandemic has already left a trail of destruction, including enormous loss of life, a global economic slump, and widespread psychological damage. Despite assiduous world-wide endeavors, an effective cure for COVID-19 is still lacking. Surprisingly, infected neonates and children have relatively mild clinical manifestations and a much lower fatality rate than elderly adults. Recent studies have unambiguously demonstrated the vertical transmission of SARS-CoV-2 from infected pregnant women to fetuses, which creates yet another challenge for disease prevention. In this review, we will summarize the molecular mechanism for entry of SARS-CoV-2 into host cells, the basis for the failure of the lungs and other organs in severe acute cases, and the evidence for congenital transmission.